Field notes, summer 1984, James Dinsmore - Dinsmore, James J.et al (1984)
Field notes with several species sighting information compiled by James Dinsmore for the Summer of 1984. It includes a clarification for a Scissor-tailed Flycatcher sighted at Wayne County, IA on May 2, 1984 by Bob Jackson. Epson - sheet feed